Refresher training workshop report on cascading gender responsive & nutrition sensitive ToT training - Ketema, Dessalegn; Nchanji, Eileen (2024)
The Refresher Training Workshop on Cascading Gender Responsive & Nutrition Sensitive Training of Trainers (ToT) took place on June 27, 2024, at Yilma Hotel, Holeta, Ethiopia. The primary objective was to develop and implement a cascading ToT program that integrates gender-responsive and nutrition-sensitive approaches. The workshop aimed to empower business coaches, local farmers and experts who will subsequently educate and support their families and communities, leading to improved gender equality and nutritional outcomes. The workshop featured thematic sessions including Contextualizing the balanced diet recipe which addresses the nutritional benefits of each ingredient and how they contribute to a balanced diet, a live cooking demonstration, highlighting food safety, preparation techniques, and time management, skill-building exercises, and collaborative group work, all designed to equip participants with the necessary knowledge and skills. As a result, participants demonstrated significant improvements in their understanding and ability to implement these approaches and developed action plans to cascade the training in their respective woredas. Overall, the workshop laid a strong foundation for widespread implementation of these critical approaches in community health programs, highlighting the need for ongoing support and resources to ensure sustained impact.